Telaah Pembelajaran Berbasis Understanding by Design pada Implementasi Kurikulum Merdeka dalam Pembelajaran Pendidikan Agama Islam - Ramadhan, Taufiq; Zahro, Ahmad; Arifin, Zaenal (Kartika: Jurnal Studi Keislaman, 2025)
This research stems from the urgency of understanding the complexity of curriculum development in Indonesia, particularly the implementation of the Independent Curriculum in Islamic Religious Education (PAI) learning at SMK PGRI 2 Kediri. The primary objective of this study is to examine the practice of the Independent Curriculum by PAI teachers, analyze the methods and strategies employed, identify the challenges faced, and assess its suitability in relation to the Understanding by Design (UbD) principle for designing learning that fosters in-depth understanding and competency achievement. This study employed qualitative methods to gather contextual data on PAI learning practices. The results show that PAI teachers have optimized the Independent Curriculum through planning based on learning outcomes and objectives, developing learning modules according to student characteristics, and implementing authentic assessments that foster Islamic character. These findings demonstrate the alignment between the Independent Curriculum and UbD, where teachers act as designer-facilitators who connect Islamic values ​​with industrial work culture, while also emphasizing that the curriculum is not merely a document, but an instructional culture to shape the Pancasila Student Profile with Islamic character.